Problems and solutions on quantum mechanics - Lim, Yung-kuo (Major American universities Ph. D. qualifying questions and solutions, 1998)
The material for these volumes has been selected from 20 years of examination questions for graduate students at the University of California at Berkeley, Columbia University, University of Chicago, MIT, SUNY at Buffalo, Princeton University and the University of Wisconsin.